Computational modelling of bone regeneration using a three-dimensional lattice approach - Byrne, Damien Paul (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2009)
Mechano-regulatory theories are indispensable for developing and understanding how mechanical forces modulate morphological and structural fitness of skeletal tissues. These theories have been incorporated into computational simulations of tissue regeneration and provide considerable predictive power, especially in bone tissue engineering. The primary objective of this thesis was to develop a method to include cellular processes in three-dimensional mechano-regulation computational models - namely proliferation, migration, cellular apoptosis and differentiation. In the first part of this work, tissue-differentiation and bone regeneration is simulated in a regular structured scaffold to investigate varying scaffold parameters on bone formation; such as porosity. Young’s modulus and dissolution rate - and this is done under low, high and ramp loading conditions. The simulations predicted that all three design variables have a critical effect on the amount of bone regeneration. In general, it was found that scaffolds conducive to osteogenesis in the initial stages of healing allow for the development of a system that will be able to withstand the applied forces as time progresses. It was therefore concluded that scaffolds must be optimised to suit site-specific loading requirements. In the second part of this work, a fracture healing model of bone regeneration was investigated. The main phases observed during healing were predicted, and the temporal changes in interfragmentary strain and bending stiffness were corroborated by comparison to experimental data and clinical results. For the first time bone healing was simulated beyond the reparative phase by modelling the transition of woven bone into lamellar bone. Bone healing was also found to be sensitive to the permeability values of woven bone. In summary, this work has further established the potential of mechanobiological computational models in developing our knowledge of cell and tissue differentiation processes during bone healing and can be used to assist optimisation of implant design and investigation of fracture treatments.
Keywords: Mechanical Engineering, Ph.D.; Ph.D. Trinity College Dublin